Pengembangan Video Pembelajaran Berbasis Animasi Materi Sistem Respirasi Kelas XI SMA - Miza Nina Adlini; Dian Kusuma Wardana (Postgraduate, University of Mataram, 2022)
Education in the 21st century is a learning system that aims to prepare a generation that prioritizes technological progress to be able to keep up with the times, one of which is to develop animated learning videos as learning media. in the development of this animated video, it makes it easier for teachers and students to deliver learning and can make learning more interesting while also making it easier for students to understand biology lessons, especially in the respiratory system material. This study aims to create a learning media in the form of an animated video that is valid, practical, and feasible. This research uses the R&D Research method. The research model is a 4D model, the research design was modified into four namely descriptions, design, development, and dissemination. Ratings on animated videos by media experts are 93.00%, material experts are 96.00%, and practitioners are 88.00%. Student assessments were obtained from a limited trial of 84.00% and a broad trial of 83.00%. Each assessment is in the product category very suitable for use in the learning process.